2007
DOI: 10.1302/0301-620x.89b11.19352
|View full text |Cite
|
Sign up to set email alerts
|

Non-invasive interactive neurostimulation in the post-operative recovery of patients with a trochanteric fracture of the femur

Abstract: We undertook a trial on 60 patients with AO 31A2 fractures of the hip who were randomised after stabilisation of the fracture into two equal groups, one of which received post-operative treatment using a non-invasive interactive neurostimulation device and the other with a sham device. All other aspects of their rehabilitation were the same. The treatment was continued for ten days after operation. Outcome measurements included the use of a visual analogue scale for pain, the brief pain inventory and Ketorolac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
26
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(26 citation statements)
references
References 39 publications
(43 reference statements)
0
26
0
Order By: Relevance
“…11 These areas are considered to be the optimal locations for the most effective application of electrical stimulation. 12,17,19,28 The low impedance of the skin over painful locations is produced by an increase in the galvanic or sympathetic skin response.…”
Section: Postoperative Rehabilitationmentioning
confidence: 99%
See 2 more Smart Citations
“…11 These areas are considered to be the optimal locations for the most effective application of electrical stimulation. 12,17,19,28 The low impedance of the skin over painful locations is produced by an increase in the galvanic or sympathetic skin response.…”
Section: Postoperative Rehabilitationmentioning
confidence: 99%
“…12,17,19,28 The low impedance of the skin over painful locations is produced by an increase in the galvanic or sympathetic skin response. 11,16,28,30 Several authors have reported that these locations correlate to myofascial trigger points, 16,17,19,28 acupuncture points, 17,19,28,30 and localized sympathetic tissue changes. 12, 13 Melzack 12 demonstrated that treating major nerve branches, trigger points, and secondary areas along an associated dermatome, in addition to the area of pain, with high-amplitude stimulation provided the most effective and sustained pain relief when compared to lower amplitude treatment delivered only at the point of pain.…”
Section: Postoperative Rehabilitationmentioning
confidence: 99%
See 1 more Smart Citation
“…Although their mechanism of action is unclear, both NIN therapy and TENS are hypothesized to work through one or both of these mechanisms as well 1518. The NIN device generates high amplitude nondamaging current impulses that stimulate C fibers and A-delta fibers thought to release neuropeptides into the bloodstream, promoting healing and inducing analgesia.…”
Section: Introductionmentioning
confidence: 99%
“…3 The analgesic effects of InterX have been attributed to a distinctive electrode positioning as well as higher amplitude and density of the applied current, compared with transcutaneous electrical nerve stimulation (TENS). 3,4 To date, 3 randomized controlled clinical trials using different models of InterX have shown advantage of this modality over placebo application in postoperative recovery from bone fractures, 4 knee replacement surgery, 5 and ankle fracture. 6 Interestingly, in a recent study, Schabrun et al 7 have shown that interactive neurostimulation therapy (NIN) may be also efficacious for managing musculoskeletal conditions, such as myofascial pain syndrome, and be of clinical significance in some patients with shoulder or NP.…”
mentioning
confidence: 99%